PERILAKU HARIAN ORANGUTAN (Pongo pygmaeus) SETELAH DILEPASLIARKAN DI HUTAN LINDUNG GUNUNG TARAK KABUPATEN KETAPANG KALIMANTAN BARAT - Sopiansah, Yusuf Eko; Prayogo, Hari; Rifanjani, Slamet (Universitas Tanjungpura, 2018)
Orangutans are the great apes that is only living in the continent of Asia. They consist of 3 species, namely Pongo pygmaeus, P. abelii, P. tapanuliensis. This has prompted much research to study about Pongo spp. However, the aim of this research is to study the daily behavior of the Borneo orangutan (P. pygmaeus) after released into its natural habitat. This research was conducted in The Protected Forest of Tarak Mountain, Subdistric of Nanga Tayap, Ketapang, West Kalimantan. The observation was done at 05.00 – 06.00 am until 16.00 – 17.00 pm, for 7 days. The results showed that the dominant activity of orangutan were eating and defecation in the morning, and nesting, moving and resting in the afternoon. Orangutan are groom when they are feeding or resting. Based on that, there was difference of orangutan behavior between after released in the nature habitat with orangutan behavior is rehabilited. This become important information about orangutan as the early efforts to conserve this species exspecially orangutan after released into nature forest.Keywords: Bornean Orangutans, Daily Behavior, Focal Animal Sampling, Protected forest of Mt Tarak